An In Vitro Study to Assess the Best Strategy for the Chemical Debridement of Periprosthetic Joint Infection - Miguel Márquez-Gómez; Marta Díaz-Navarro; Andrés Visedo; Rama Hafian; José Matas; Patricia Muñoz; Javier Vaquero; María Guembe; Pablo Sanz-Ruíz (MDPI AG, 2023)
Irrigation and debridement using an irrigation solution is a fundamental step during the surgical treatment of both acute and chronic periprosthetic joint infection (PJI). However, there is no consensus on the optimal solution, nor is there sufficient evidence on the optimal irrigation time and combination of solutions. Therefore, it is necessary to determine which solution or combination of solutions is most efficacious against biofilm, as well as the optimal irrigation time. We conducted an experimental in vitro model by inoculating stainless steel discs with ATCC strains of methicillin-susceptible Staphylococcus aureus, methicillin-resistant S. aureus, Pseudomonas aeruginosa, and a clinical strain of Staphylococcus epidermidis. The discs were all irrigated with commonly used antiseptic solutions (10% and 3% povidone iodine, hydrogen peroxide, 3% acetic acid, and Bactisure™) for 1 min, 3 min, and 5 min and their combinations for 9 min (3 min each) vs. sterile saline as a positive control. We evaluated the reduction in biofilm based on colony-forming unit (cfu) counts and in combination assays, also based on cell viability and scanning electron microscopy. All antiseptics alone reduced more than 90% of cfu counts after 1 min of irrigation; the worst results were for hydrogen peroxide and 3% acetic acid. When solutions were sequentially combined, the best results were observed for all those starting with acetic acid, in terms of both reduction of log cfu/mL counts and viable cells. We consider that a combination of antiseptic solutions, particularly that comprising the sequence acetic acid + povidone iodine + hydrogen peroxide, would be the best option for chemical debridement during PJI surgery.